Environmental Health Risk Hazardous Factors to Living Species - Larramendy, Marcelo L.; Soloneski, Sonia (IntechOpen, 2016)
This book, Environmental Health Risk - Hazardous Factors to Living Species, is intended to provide a set of practical discussions and relevant tools for making risky decisions that require actions to reduce environmental health risk against environmental factors that may adversely impact human health or ecological balances. We aimed to compile information from diverse sources into a single volume to give some real examples extending concepts of those hazardous factors to living species that may stimulate new research ideas and trends in the relevant fields.